Ann Oakley: new learning and global influence from working across conventional boundaries (UCL Press, 2023)
Ann Oakley, pioneering social researcher for nearly 60 years, is Professor of Sociology and Social Policy at IOE (Institute of Education), UCL's Faculty of Education and Society (University College London, UK). This article explores the innovation and influence of her work and the work of her close colleagues at the Social Science Research Unit (SSRU) and its Evidence for Policy and Practice Information and Coordinating Centre (EPPI-Centre). It describes advances in research and knowledge that have their roots in listening to what women have to say about their lives. The resulting novel research methods have straddled academic boundaries - between qualitative and quantitative methodologies, between disciplines, and between academia and wider society - to enhance understanding of complex social issues and approaches to addressing them within the public sector. The impact of this work is seen in terms of influencing science, knowledge management, policy decisions, professional practice and the general public. These achievements come from approaches that are outward looking and straddle academic disciplines to produce evidence that is relevant to policymaking and to practice, with the ultimate aim being to improve day-to-day life.